Politicization of the Concept of Heterodoxy as a Socio-Religious Construction: From Social to Political - Coşkuner, Murat (Journal of Alevism-Bektashism Studies, 2020)
Ruling elites who have undertaken political tasks such as building a new society or stabilising the existence of the current society, have tried to prevent political struggles that may arise within society, especially by emphasizing the interdependence of social groups. The literature produced in accordance with this ideological goal was also either created using sociological terminology with politic qualifications pushed back, or swallowed by theological perspectives. This paper, which will try to show that the concept of heterodoxy used by the ruling elites with the aim of creating a modern and national society for the Turkish nation-state is also constructed in the same context, will argue that this started to grow from the late 1980s. The paper will show that the popular press which emerged and began to develop in these years, didn’t make a fundamental distinction between the categories of religion and politics and was produced by authors of Alevi origin, had a significant impact on the existing transformation. It will be suggested that the writing in question, which doesn’t have academic qualifications, still caused the transformation of the usage of the heterodoxy and orthodoxy concepts in the academic field, and ensured that these concepts are considered along with the important terms of political literature such as resistance, tyranny, power and governed masses. This paper, focused on the role of the press that Alevi communities started to produce since the late 1980s in the reinterpreting of the heterodoxy and orthodoxy concepts within the academic field, will contribute to the studies of Sociology in Turkey, and also show what kind of results the despised and ignored popular press of these communities produced for the studies of political science.Within the scope of the paper, the first section will analyse the authors who had influence on the socio-religious construction of the concepts in question. The following section will emphasize what kind of basis the press created in the reinterpreting of the heterodoxy and orthodoxy concepts, by discussing the emergence of the Alevi press. The last section will address the examples of these concepts, which have started to be political, in the scientific field.
Keywords: Heterodoxy; orthodoxy; politicization; society; Alevi press